Chemical composition of rain and fog water collected in the Monteverde biological reserve - Vásquez Morera, Tatiana (2012)
We determined the chemical composition of rain and fog water in three sampling sites in the Monteverde Biological Reserve, Puntarenas, between October 2009 and January 2010. Due to its state of conservation, and its geographic location on the continental divide, the Monteverde Biological Reserve offers an ideal study site for the environmental chemical monitoring of tropical ecosystems, which includes the analysis of rain and fog water. Samples of for water were collected using Teflon lined samplers, while rainwater was collected using simple and cascade rain water samplers. In both types of water, most relevant ionic species (H3O+, NH4 +, Ca2+, Mg2+, K+, Na+, Cl-, NO3 - and SO4 2-) were analyzed using ion chromatography.  The average concentrations of these species in the rainwater were between 0,54 ± 0,02 μeq L-1 and 101 ± 3 μeq L-1, while in the fog water ranged between 1,00 ± 0,02 μeq L-1 and 93 ± 4 μeq L-1. We also present the ionic balance and the enrichment factors with respect to the sea and soil for both types of samples.